2008
DOI: 10.1007/s11239-008-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of non-steroidal anti-inflammatory drugs with outcomes in patients with ST-segment elevation myocardial infarction treated with fibrinolytic therapy: an ExTRACT-TIMI 25 analysis

Abstract: Among STEMI patients treated with a fibrinolytic agent and aspirin, use of NSAIDs in the week preceding the incident event was associated with a higher incidence of MI, the composite of death and MI as well as the composite of death, MI, severe heart failure and shock at 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Despite the proven anti-inflammatory effect of glucocorticoids, it has been reported that their employment could be detrimental due to secondary effects like volume retention, edema, hyperglycemia, and muscular atrophy, preventing its employment in patients with myocardial infarction [17]. The prescription of commonly used NSAIDs has been limited due to the delayed appearance of ischemic necrosis and imminent risk of developing aneurism and rupture [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the proven anti-inflammatory effect of glucocorticoids, it has been reported that their employment could be detrimental due to secondary effects like volume retention, edema, hyperglycemia, and muscular atrophy, preventing its employment in patients with myocardial infarction [17]. The prescription of commonly used NSAIDs has been limited due to the delayed appearance of ischemic necrosis and imminent risk of developing aneurism and rupture [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, potent anti-inflammatory treatment with glucocorticoids was associated with impaired myocardial healing, development of ventricular aneurysms and high risk of ventricular rupture in clinical studies (53,54). Similar detrimental effects were observed following treatment with non-steroidal anti-inflammatory drugs (55). In consequence, glucocorticoids and non-steroidal anti-inflammatory drugs are contraindicated in patients with AMI by the current clinical guidelines (56).…”
Section: Anti-inflammatory Therapeutic Approaches In Amimentioning
confidence: 96%
“…• Нестероидные противовоспалительные средства (за исключением низких доз АСК** в качестве антиагреганта и средних доз ACK** для лечения перикардита) не рекомендуются при ИМпST из-за неблагоприятного влияния на риск сердечно-сосудистых событий [200][201][202].…”
Section: еок Iiab (уур B удд 3)unclassified